2017
DOI: 10.21511/imfi.14(2-2).2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Failure prediction of government funded start-up firms

Abstract: This study aims to create a prediction model that would forecast the bankruptcy of government funded start-up firms (GFSUs). Also, the financial development patterns of GFSUs are outlined. The dataset consists of 417 Estonian GFSUs, of which 75 have bankrupted before becoming five years old and 312 have survived for five years. Six financial ratios have been calculated for one (t+1) and two (t+2) years after firms have become active. Weighted logistic regression analysis is applied to create the bankruptcy pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These analyses show that traditional bankruptcy prediction models failed to predict the financial condition of small businesses. The same author, in cooperation with Lukason (Lukason and Käsper 2017), expanded his research in the field of forecasting bankruptcy risk by considering all start-ups that received government grants in the period [2004][2005][2006][2007][2008][2009][2010][2011][2012][2013]. Upon selection, data were collected for 417 companies, based on which models were built using logistic regression.…”
Section: Estoniamentioning
confidence: 99%
“…These analyses show that traditional bankruptcy prediction models failed to predict the financial condition of small businesses. The same author, in cooperation with Lukason (Lukason and Käsper 2017), expanded his research in the field of forecasting bankruptcy risk by considering all start-ups that received government grants in the period [2004][2005][2006][2007][2008][2009][2010][2011][2012][2013]. Upon selection, data were collected for 417 companies, based on which models were built using logistic regression.…”
Section: Estoniamentioning
confidence: 99%
“…Thus, for instance, for export support agencies, it would be especially important to detect which firms would internationalize fast, and to support such firms. Still, extant research indicates that funding decisions can be associated with high failure rates [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, FR-Pattern 1 firms were not subject to any remarkable liabilities concerning their financial indicators, which enables to hypothesize that in a financial sense, around half of the young exporters could be characterized with the term "born to survive" (in contrast to "born dead" firms in . Based on values of financial ratios, FR-Pattern 1 firms were more viable during the post-foundation time than an average Estonian young firm, when compared with Lukason and Käsper (2017). In addition, the same argument holds when comparing the ratio values with the same figures with an average European SME in a population of 5.75 million firms (Altman et al, 2017).…”
Section: Failure Risk Patternsmentioning
confidence: 73%
“…Since D' Aveni (1989), studies about failure risk patterns have mostly concentrated on older firms. Only a few studies Lukason and Käsper, 2017) have recently focused on young firms' failure risk patterns. These studies have concluded that the performance of most new ventures is modest, while very poor or very successful firms form a minority, but failing or surviving young firms are not well distinguishable based on their financial performance.…”
Section: Rq1 Which Internationalization Patterns (I-patterns) Exist Among Young Exporters?mentioning
confidence: 99%